Pemilihan Metode Intensitas Hujan Yang Sesuai Dengan Stasiun Hujan Pekanbaru - Febrira Ulya Astuti; Andy Hendri; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The rainfall intensity is the depth of water per unit time. Rainfall intensity can also be approached by using methods of Mononobe, Van Breen, Haspers Weduwen and Bell Tanimoto. The result of those methods would be compared with intensity of ARR data. The research was conducted to the Siak basin at Pekanbaru rainfall station. Error square mean root peak-weight test would be applicated to calculate the deviation. The result of this research showed that Haspers Weduwen and Van Breen method fitted the observed ARR data. The return period years of 2, and 5 resulted in rainfall intensity 6,4219 and 7,9265 by using error square mean root peak-weighted test. Rainfall intensity for the return period is the method of Haspers Weduwen. The return period years of 10, 25, 50 and 100 resulted in rainfall intensity 8,3962; 14,6991; 20,9080 dan 27,7208 by using error square mean root peak-weighted test. And rainfall intensity for the return period is the method of Van Breen. In general, the method according to the station data Pekanbaru is the method of Van Breen. Because it has an average error smallest than the other methods.  Keywords: Rainfall intensity, Mononobe, Van Breen, Haspers Weduwen, Bell Tanimoto, peak weighted root mean square error test.